Direito e religião: gênese linguística na construção da ética - Santos, Abílio Osmar dos (2024)
The study proposes a return to the linguistic genesis of Law and Religion and intends to launch a new investigative theme on the philosophical meaning in the construction of ethics. The main objective is to enable both a better understanding of each of these areas and, mainly, a better understanding of what we, humans, are, what constitutes us and how we constitute ourselves for the construction of ethics. The idea of work permeates connections from the perspective of language, since both law and religion are essentially linguistic structures produced in different cultural contexts, but which maintain relationships to shape human conditions and actions. It uses the Phenomenological-Hermeneutic method, as developed by Martin Heidegger. Thus, ethics brings responsibility for taking care of oneself, seeks a new relationship with the truth, as they are constructed in language, they are never completely closed, but always demand updating, so that they continue to fulfill their function of enabling the social life is constituted and, especially, by a non-extreme vision that degenerates religion and law